Design of learning simulation for the first and second law of thermodynamics - Faiz Husaini Khairi Izwan, 1989-, author; Khairiyah Mohd. Yusof, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - Universiti Teknologi Malaysia, 2012